Pelatihan Pengembangan Multimedia Interaktif Guna Mengoptimalisasi Pembelajaran Matematika SD - Kurniawati, Rissa Prima; Rulviana, Vivi; Laksana, M. Soeprijadi Djoko; Pratama, Ditto Putra (Politeknik Penerbangan Indonesia Curug, 2022)
Education is one of the important sectors in the progress of the nation. The higher the quality of education, the better the learning process carried out so that it will also have an impact on improving the quality of teachers and students. In improving the quality of students, teachers need models and learning media that are interesting and in accordance with the material being taught. Based on the observations, it is known that most of the teachers still teach by writing on the blackboard, explaining the material without using the media. But there are also those who use paper media in teaching mathematics in class. This is what makes students difficult in learning mathematics and solving math problems. The method used is the training method. The training participants were teachers at SDN Purwosari 2, Kwadungan District, Ngawi, East Java. It is hoped that through this activity, all training participants can create interesting, creative, and innovative interactive multimedia in mathematics lessons. So that students can understand mathematical material well, students no longer have difficulty in learning mathematics, and can solve mathematical problems appropriately.